Das Modell zur bestimmung von phrasemen der Bewertungskategorie Affekt/A model for defining phrasemes in the affect category of appraisal theory - Perić, Marija; Pavić Pintarić, Anita (Jezikoslovni zapiski, 2018)
This paper investigates phrasemes as language means for expressing affect within the concept of appraisal theory developed by Martin and White (2005). Phrasemes do notexclusively express emotions explicitly, but in a certain context. We propose a model for determining phrasemes in the affect category of appraisal theory based on four factors. The material for testing the model is excerpted from dialogues in the novel Helden wie wir (Heroes like Us) by Thomas Brussig.